Aspects concerning the lengths of the excluded shareholder’s liability towards third parties in the case of limited liability companies in Romania - Andreea Stoican (Juridical Tribune, 2016)
In the current context of reinventing the trading company law, at the end of a lengthy and extremely difficult economic crisis, when every participant in the economic life tried to find their own way to adapt and make their activity survive the new social and commercial realities, not few were the cases when some of the Shareholders were excluded and their liability was drawn onto the legal person itself. Nevertheless, there is a type of legal liability of the former Shareholders, excluded from the Company, that still is quite deficiently regulated and, despite the sound argumentation and comprehensive regulation of Law no. 31/1990, it fails to provide a clear and detailed explanation of the consequences, namely, of the consequences the exclusion of a Shareholder has over the Third Parties of good-faith that the legal person (the Company) had or continues to have legal relations with. This paper thus aims at analysing one of the main effects of excluding Shareholders from the company, namely the extent of their liability towards the Third Parties, and it is structured in five parts, as follows: 1) Introduction, 2) About the Shareholders’ exclusion, 3) The effects of excluding a Shareholder from the Limited Liability Company, 4) The excluded Shareholder’s liability towards the Third Parties and 5) Conclusions.